Familiares ouvintes de sujeitos surdos: reflexões sobre suas interações comunicativas - Cappellini, Michele Toso (Universidade Federal de São Carlos, 2019)
Subject of recent scientific research, the deafness is been noteworthy nowadays. However the wattled relationships between listening relatives and deaf people unfold an incipiently treated topic that needs further study. The family is the first and the nearest social group that the person keeps the most intimate relationship, and this relation to influence the global development of the person directly, affecting aspects such as language, tongue and the formation of subjectivity. Thus, the present research had as general objective to analyze aspects of a process of reflection beside listening members family of deaf subjects about their communicative interactions in home environment, based on the historical and cultural approach of Vigotski. The specific objectives were: to investigate the communicative interactions between listening relatives and the deaf person in the home environment; to contribute with the study about the sensitive instruments for the evaluation of face to face communication in different contexts and with different audiences; to analyze the contributions of the process of reflection together to the listening relatives of deaf subjects for their communicative interactions. Six families participated of the research and each family is constituted by listening members and a deaf person who is enrolled at a Public Municipal School which develops a Bilingual Inclusive Education Program. The methodological course consisted on three stages: at the first, to analyze the communicative interactions in the daily life of the families; then to accomplish a reflection process with the family members about these interactions – stage called advisory – and finally at the third stage, it was made a new analysis of the communicative interactions between listening members family with their deaf members, with the purpose of identify contributions of the advisory to the interactions. All the stages were filmed and guided by the instrument "Evaluation Scale of Oral Language in the Family Context (EVALOF)". As a result, we verified that the most frequent form of communication observed at the first stage of the research, was bimodal communication. There was improvement in the communicative interactions on all the families after the advisory, whereas the speeches became more structured in “Libras” and, consequently, there was the presence of the other members of the family involved in the learning of this language. The Scale has become a favorable instrument to conduct the observations in a home environment; and its the most relevant point is its use as a reflexive instrument for families. Some adjustments were proposed for the studied public in order to contribute with the researches in the area. Finally, the advisory process enabled to listen the relatives of the deaf person; this was essential to resignify their relationships with the deaf person and the “Libras”. This support must be and can be assumed by the Bilingual Education Institutions for Deaf providing partnership positive practices between the family and the school, as co-responsible for the constitution of bilingual subjects.
Keywords: Surdez; Língua de sinais; Interação familiar; Educação bilíngue; Educação Especial; Deafness; Sign language; Family interaction; Bilingual educaction; Special Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO